PELAKSANAAN JAMINAN SOSIAL TENAGA KERJA TERHADAP PEKERJA/BURUH PADA PT. LAJU PERDANA INDAH UNIT PG PAKIS - , WIRA ALJAUHARI PURNAMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Labor as an agents of development is one of the driving factors that have a role and a very important position in the national development process. According to this, it is necessary to the development of employment in accordance with the terms set forth in the constitution in 1945 which said that every citizen has the right to work and decent living for humanity. Labor in carrying out their duties often encounter many obstacles and social risks that may reduce the ability to work, it can even result in the loss of their ability to work and can affect their lives. The activities of labor in national development efforts in Indonesia and the higher technology used by various sectors of business activity in the globalization era causes increased risk suffered by workers who can threaten the prosperity, health and safety , so that it is necessary need protection for workers by creating a social insurance policy for workers. Implementation of labors duties who work in dangerous conditions is possible occurrence of work accidents. The accidents are not only caused by the negligence of workers, but it may possibly occur due to the use of technology and environmental conditions. Therefore, in order to maintain the safety and prosperity of the workers of the dangerous condition, there needs to be insured against hazards or accidents at work for every worker.